2017
DOI: 10.35762/aer.2017.39.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Formaldehyde in Gross Anatomy Laboratory: Area-Based and Exposure Levels, Ventilation, Health Risk and Clinical Symptoms

Abstract: Formaldehyde is commonly used in embalming solution in medical fields to preserve tissues. Formaldehyde vapor released from cadavers during dissection practice can adversely affect students and instructors in gross anatomy laboratories. Therefore, this study investigated formaldehyde concentrations in a gross anatomy laboratory of Mahasarakham University, Thailand. Area-based sampling was conducted for three scenarios: (1) a laboratory cleaning period, (2) three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
2
3
0
Order By: Relevance
“…Some individuals were highly sensitive to the FA while others were more resistant and had no reaction to the same level of exposure [ 40 ]. In our study, the most frequent complaint reported by the exposed students was the unpleasant smell (78.8%) ( Figure 9 ), and this occurrence is consistent with some previous studies which also reported this symptom as the most predominant one at 68% [ 21 ], 80% [ 41 ], 77% [ 42 ], 57.5% [ 35 ], 91.2% [ 43 ] and, 70.3% [ 44 ]. This common finding simply reflects that FA exposure is mainly by inhalation during the dissection sessions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Some individuals were highly sensitive to the FA while others were more resistant and had no reaction to the same level of exposure [ 40 ]. In our study, the most frequent complaint reported by the exposed students was the unpleasant smell (78.8%) ( Figure 9 ), and this occurrence is consistent with some previous studies which also reported this symptom as the most predominant one at 68% [ 21 ], 80% [ 41 ], 77% [ 42 ], 57.5% [ 35 ], 91.2% [ 43 ] and, 70.3% [ 44 ]. This common finding simply reflects that FA exposure is mainly by inhalation during the dissection sessions.…”
Section: Resultssupporting
confidence: 91%
“…Since irritation is one of the characteristics of FA [ 12 ], symptoms of eye and upper respiratory tract irritations such as eye itchiness, excessive lacrimation, eye redness, blurred vision and nasal symptoms were frequently observed in our study and other previous studies [ 21 , 35 , 42 , 43 , 45 ].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Studies have found that fan-based ventilation in dissection halls has resulted in higher levels of formaldehyde (FA) [35]. Other reports have shown that personal exposure to FA can be higher than indoor levels when using air conditioning in anatomy halls [36,37,38].…”
Section: Discussionmentioning
confidence: 99%